1993
DOI: 10.1159/000187280
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Mitral and Aortic Valve Sclerosis for Survival in End-Stage Renal Disease on Continuous Ambulatory Peritoneal Dialysis

Abstract: To determine whether mitral valve or anular sclerosis or calcification (MC) is associated with reduced survival in patients with end-stage renal disease on continuous ambulatory peritoneal dialysis (CAPD), 53 CAPD patients were followed with echocardiography and Doppler echocardiography over 35 months. Both nonsurvivors and survivors with MC had higher systolic blood pressure before CAPD and calcium-phosphorus products during CAPD treatment than patients without MC (p < 0.05). Serum calcium and phosphorus conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Notably, the combined presence of AVS and MAC was more strongly associated with an increased risk of all-cause and CVD mortality than the presence of either item alone. Collectively, the results of this study complement and expand previous observations on the value of AVS and MAC for predicting mortality both in the general population and in other nondiabetic high-risk patient populations (1,49,18). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Notably, the combined presence of AVS and MAC was more strongly associated with an increased risk of all-cause and CVD mortality than the presence of either item alone. Collectively, the results of this study complement and expand previous observations on the value of AVS and MAC for predicting mortality both in the general population and in other nondiabetic high-risk patient populations (1,49,18). …”
Section: Discussionsupporting
confidence: 82%
“…However, AVS shows epidemiologic and histopathologic similarities to coronary atherosclerosis (2,3). In addition, recent large prospective studies have suggested a strong association between AVS and cardiovascular disease (CVD) outcomes both in the general population (1,46) and in nondiabetic high-risk patient populations such as patients with hypertension (7), coronary artery disease (8), and chronic kidney disease (9). …”
mentioning
confidence: 99%
“…Mesodiastolic or presystolic murmurs may be ascribed to functional stenosis of the mitral valve. Systematic echocardiography in adult patients with ESRD has shown that valvular disease is observed mainly in the presence of cardiomegaly and overhydration in association with left atrial and ventricular dilatation [6]. The functional nature of mitral and tricuspid regurgitation was recently proven by disappearance of these lesions after intensified ultrafiltration in hemodialysis patients [7].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH), enhanced aortic valve calcification, and increased wall stiffening and intima media thickening of the large arteries have all been recognized as independent risk factors for acute death in these patients [1,2,3,4]. Until recently, there were only limited data on cardiovascular disease in children with ESRD.…”
Section: Introductionmentioning
confidence: 99%